Warrior marks : female genital mutilation and the sexual blinding of women - Walker, Alice; Parmar, Pratibha (New York : Harcourt, 1993)
Fonds Suzan Daniel (FSD)
Engels
Monografie
Keywords: genitale verminking; vrouwen